Chalcone based dithiocarbamate derivative incorporated sol-gel for the removal and pre-concentration of aqueous mercury(II) ion / Khor Soo Wei - Khor , Soo Wei (2018)
This study demonstrated the application of chalcone based dithiocarbamate derivative as metal capturing ligands for the removal and pre-concentration of mercury ion (Hg2+). Chalcones are a group of naturally occurring compounds, which can be extracted from fruits, vegetables, plants, and spice. In the first part of this work, chalcone was first chemically modified to produce dithiocarbamate derivative, 3-oxo-1,3-diphenylpropyl-2-(naphthalen-2-ylamino) ethylcarbamodithioate (ODPPNE). After that, chalcone incorporated sol-gel (SG-C) and ODPPNE incorporated sol-gel (SG-ODPPNE) were prepared and used as adsorbents to remove Hg2+. The result showed that with the presence of dithiocarbamate functional group, SG-ODPPNE exhibited the high selectivity toward Hg2+ adsorption as compared to other metal ions. The effect of operating conditions (such as the size of adsorbent, adsorbent dosage, contact time, the initial concentration of Hg2+ and pH of solution) were examined for the adsorption of Hg2+ by SG-ODPPNE. The adsorption data were fitted well to Langmuir isotherm, and the monolayer adsorption capacity was found to be 13.5 mg/g. In the adsorption kinetic study, the obtained data were well fitted to pseudo-second order model. According to intraparticle diffusion model, the adsorption process of Hg2+ by SG-ODPPNE involves film diffusion, intraparticle diffusion, and equilibrium stages. For the second part of this study, ODPPNE incorporated silica was coated onto magnetic nanoparticle (ODPPNE@MNP). This ODPPNE@MNP was used as the solid phase in magnetic dispersive micro-solid phase extraction method (D-